The effect of environmental degradation on the characterisation of automotive clear coats by infrared spectroscopy - van der Pal, Karin; Sauzier, Georgina; Maric, M.; van Bronswijk, Wilhelm; Pitts, K.; Lewis, Simon (Elsevier, 2015)
This paper presents a study into the chemical changes occurring within automotive clear coats as a result of environmental weathering, and their potential effect upon the characterisation of samples using infrared spectroscopy combined with chemometric modelling. Testing of three samples, collected from separate vehicles, exposed to the outside environment revealed no changes in model predictions over a 175 day period; however, incorrect predictions were observed following 435 days of exposure. Inspection of the corresponding infrared spectra revealed that these changes were likely due to the hydrolysis and photodegradation of polymer chains present in the clear coat, which were not observed in samples stored away from the outside environment over a one-year period. Analysis of previously weathered samples using synchrotron infrared microscopy found these changes occurred in a top-down fashion rather than within the bulk of the clear coat. This indicates that although weathering may affect the surface characterisation of clear coats over time, the targeting of deeper portions of the clear coat layer may still provide useful information as to the identity of the vehicle.